UNMASKING THE SCAR OF COVID-19 PANDEMIC ON THE TRADITIONAL GOLD JEWELLERY INDUSTRY IN ASHANTI, GHANA FOR QUICK RECOVERY AND GROWTH OUTPUT - Peggy Fening; Isaac Kwabena Agyei (Lafadz Jaya Publisher, 2023)
The unprecedented cataclysm of the Covid-19 pandemic has been severely felt in all sectors of the economy globally and especially in SMEs of developing countries including Ghana. While evidence on the impact of the pandemic on SMEs in developed countries is growing, that of the developing countries remain scanty, particularly the dynamics within a single enterprise. This study addresses some aspect of this gap by drawing on a representative survey of 150 traditional gold jewellery industries in the Kumasi Metropolis of Ghana. Data obtained for this study were acquired through the use of questionnaire and personal interviews and analyzed using SPSS version 22. Descriptive statistical tools such as frequency and percentage were used to analyze the facts sought from questionnaire. The study recorded an overall response rate of 96.5%. The general outcome of the study showed that the majority of the craftsmen are battling to bounce back to normalcy for the three years of the post Covid era. Sixteen percent (16%) out of the 20% of the jewellery workshops that shut down their operations during the outbreak of the pandemic have not recovered. Those affected have ventured into other businesses including petty trading and transport. Some of the evidential factors militating against the post Covid 19 recovery of the industry included, high cost of raw materials, shortage of cash flow, high inflation rates and change in consumer behaviour. Sixty eight percent (68%) of the craftsmen interviewed have a positive future outlook of their businesses, 18% are uncertain, while the remaining 14% have no hope, citing loss of startup capital as reasons for their perception. The study proposes a new policy direction of boosting the technology direction of the industry and also providing incentives for startups to innovate and grow at a faster rate.